DETERMINANTS OF PHYSICAL ACTIVITY BEHAVIOR IN HIGH SCHOOL ADOLESCENTS IN GRESIK REGENCY - Afina Puspita Zari; Ira Nurmala; Muji Sulistyowati; Dayinta Annisa Syaiful (The Indonesian Journal of Public Health, 2025)
Introduction: Obesity is one of the global problems as declared by the WHO. In Indonesia, obesity is continuously rising over the years with 12.2% in teenagers aged >15. Therefore, physical activity is one of the prevention efforts to reduce obesity to create a healthy and prosperous life in accordance with the SDGs indicators to campaign for a healthy lifestyle and strive to achieve prosperity for the world community. Aims: This study aims to analyze the factors of physical activity behavior in high school teenagers in Gresik Regency. Method: This study implemented a quantitative approach with the cross-sectional method. The researchers obtained  samples for about 360 adolescents with a stratified proportional random sampling technique. The data collection was gathered by completing online questionnaires through Google Forms. The data analysis method employed in this study was the Chi-Square test by observing the relationship in each variable. Result: This study’s result indicates a relationship between gender, social support, and supportive situations with physical activity behavior. However, the age variable demonstrates no relationship with physical activity behavior. Conclusion: Most adolescents in the Senior High Schools of Gresik Regency exhibit moderate physical activity. It means that the majority of respondents have performed physical activity within seven days. Social support, including family support, school support, and peer support, as well as the existence of supportive facilities in the environment around adolescents, can increase physical activity behavior in adolescents.